THE IMPLEMENTATION OF BCBL MODEL ON INTEGRATED ECONOMIC EXPLORATION TO DEVELOP XXI CENTURY SKILLS - APRULLAH, MUHAMMAD PUTRA; FUADI, RAIDA; SAYUTHI, MUHAMMAD; ADRIA, AGUS; JULNADI, SALSABILLA (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This paper aims to find out how the application of the Brain Collaborative Based Learning (BCBL) learning model on Integrated Economic Exploration material to develop XXI Century Skills of Class X-3 MAN 1 Banda Aceh students. The application of this learning model involved 39 students. The achievement of learning targets for Integrated Economic Exploration material using the Brain Collaborative Based Learning (BCBL) learning model still varies. This learning model increases student motivation in the literacy of integrated economic exploration material on environmental, social and religious moderation issues. The absorption and target achievement of the curriculum on integrated economic exploration material with the target achievement of 21st century skills is 92.31%. Three out of thirty-nine students in class X-3 did not meet the completeness of the learning objective achievement criteria score (KKTP: 78-80). The Brain Collaborative Based Learning (BCBL) learning model is believed to be able to contribute to the development of XXI century generation skills in welcoming the Sustainability Development Goals. ABSTRACTThis paper aims to find out how the application of the Brain Collaborative Based Learning (BCBL) learning model on Integrated Economic Exploration material to develop XXI Century Skills of Class X-3 MAN 1 Banda Aceh students. The application of this learning model involved 39 students. The achievement of learning targets for Integrated Economic Exploration material using the Brain Collaborative Based Learning (BCBL) learning model still varies. This learning model increases student motivation in the literacy of integrated economic exploration material on environmental, social and religious moderation issues. The absorption and target achievement of the curriculum on integrated economic exploration material with the target achievement of 21st century skills is 92.31%. Three out of thirty-nine students in class X-3 did not meet the completeness of the learning objective achievement criteria score (KKTP: 78-80). The Brain Collaborative Based Learning (BCBL) learning model is believed to be able to contribute to the development of XXI century generation skills in welcoming the Sustainability Development Goals.